Comparison of long-read sequencing and MLPA combined with long-PCR sequencing of CYP21A2 mutations in patients with 21-OHD - Lan, Tian; Wang, Jin; Chen, Kaibi; Zhang, Jianru; Chen, Xiaohong; Yao, Hui (Frontiers in Genetics, 2024)
Background 21-Hydroxylase deficiency (21-OHD) is caused by mutations in the CYP21A2 gene. Genetic testing for 21-OHD is currently facing challenges. Moreover, there are no comparative studies on detecting CYP21A2 mutations by both secondgeneration sequencing and long-read sequencing .Objective To detect CYP21A2 variations in 21-OHD patients using targeted capture with LRS method based on the PacBio Sequel II platform.Methods A total of 67 patients with 21-OHD. The full sequence of CYP21A2 gene was analyzed by targeted capture combined with LRS based on the PacBio Sequel II platform. The results were compared with those of long-polymerase chain reaction (Long-PCR) combined with multiplex ligation probe amplification (MLPA) detection. The correlation between different genotype groups and clinical typing was observed.The study analyzed a total of 67 patients. Among them, 44 (65.67%) were males and 23 (34.33%) were females, with a male-to-female ratio of approximately 1.9:1. A total of 27 pathogenic variants were identified in the 67 patients, of which micro-conversion accounted for 61.9%, new variants of CYP21A2 accounted for 8.2%; deletion accounted for 22.4% (CYP21A2 single deletion and chimeric TNXA/TNXB accounted for 12.7%, chimeric CYP21A1P/CYP21A2 accounted for 9.7%); and duplication accounted for 3.0% (CYP21A2 Gene Duplication). I2G was the most common variant (26.9%). Targeted capture LRS and MLPA combined with Long-PCR detection of CYP21A2 mutations showed 30 detection results with differences. The overall genotype-phenotype correlation was 82.1%. The correlation coefficient rs between the severity of the phenotype and the genotype group was 0.682 (P < 0.05).Targeted capture combined with LRS is an integrated approach for detecting CYP21A2 mutations, allowing precise determination of connected sites for multiple deletions/insertions and cis/trans configurations without analyzing parental genomic samples. The overall genotype-phenotype correlation for 21-OHD is generally strong, with higher associations observed between genotype and phenotype for group Null, A, and B mutations, and larger genotype-phenotype variation in group C mutations. Targeted capture with LRS sequencing offers a new method for genetic diagnosis in 21-OHD patients.